Prospects and Potential of Buckwheat (Fagopyrum spp) Production in Nepal: A Review - Adhikari, Bishnu Bilas (Journal of the Institute of Agriculture and Animal Science, 2023)
Buckwheat is one of the important but underexploited crop of Nepal. It ranks 6th position as a staple food crop and is cultivated from Terai to mid hills and mountains. It is cultivated as summer crop in mountains, autumn and spring crop in mid-hills and winter crop in Terai and inner terai. The major buckwheat producing districts of Nepal are Mustang, Humla, Dolpa, Mugu, Kalikot, Jumla, Rukum, Rolpa, Jajarkot, Kavre, Dolakha, Solukhumbu, Okhaldhunga and Taplejung. It is considered as a short duration, eco-friendly, drought tolerant, wider adoptive and rainfed loving crop with minimal requirement of plant nutrients, tilling, plant protection measures and other management practices. It plays an important role in the food and nutritional security of the people living in remote rural areas. Two buckwheat species; Fagopyrum. esculentum (Mithe phaper) and Fagopyrum. tataricum (Tite phapar) are cultivated in Nepal. It can withstand against various kinds of biotic and abiotic stresses and fit well in various multiple cropping systems. The area, production and productivity of buckwheat in Nepal during fiscal year 2021/022 is 13875 ha, 15917 tons and 1.15 tons ha-1, respectively. Several factors such as frost, drought, lack of high yielding varieties, lodging, self-incompatibility, female sterility, indeterminant growth habit, shattering is responsible for low yield. To increase the area, production and productivity of buckwheat in Nepal, immediate attention should be given by the researchers, development workers, local governments, and policy makers by developing and advocating location specific scientific interventions and policies.